Colony Composition of Two Malaysian Ponerine Ants, Platythyrea Tricuspidata and P. Quadridenta: Sexual Reproduction by Workers and Production of Queens (Hymenoptera: Formicidae) - Fuminori Ito (Psyche: A Journal of Entomology)
Colonies of ponerine ants Platythyrea quadridenta and P. tricuspidata were collected in the rainforest of West Malaysia. Two colonies of P. tricuspidata were composed only of workers, and three and eight workers were inseminated per colony, respectively. However, active ovaries were found in one of the three, and two of the eight mated workers. P. quadridenta also exhibited sexual reproduction by workers, and there were many sterile mated workers. The two largest colonies of P. quadridenta produced alate queens. The significance of queen production and worker sexual reproduction are discussed.